Best Practices in Hospitality and Tourism Marketing and Management A Quality of Life Perspective - Campón-Cerro, Ana María; Hernández-Mogollón, José Manuel; Folgado-Fernández, José Antonio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume analyses the positive effects that tourism generates on resident's quality of life, and how this influences tourists' quality of life as they enjoy an enriching experience in the destination they visit. It provides significant theoretical and empirical contributions, as well as, case studies related to quality of life in hospitality and tourism marketing and management. This volume is the result of the effort that many researchers from all over the world have done to spread some new light on this outstanding research line and add knowledge on the relationship between tourism and quality of life of both residents and tourists. This last is highlighted as a fundamental factor to take into account for the development of new tourism practices. This volume is a true reference for researchers, students and professionals working in tourism marketing and management.
Part I. Introduction -- Chapter 1. Quality of Life (QOL) in Hospitality and Tourism Marketing and Management: an Approach to the Research Published in High Impact Journals (Ana María Campón-Cerro) -- Part II. Quality of Life in Tourism and its Impact on Local Community -- Chapter 2. Tourism Marketing as a Tool to Improve Quality of Life among Residents (Natalia Vila - Lopez) -- Chapter 3. What is the Nature of the Relationship between Tourism Development and the Quality of Life of Host Communities? (Eunju Woo) -- Chapter 4. Tourism Development as a Resident-Tourist Exchange Process. An Economic Theoretic Interpretation (Salvatore Bimonte) -- Chapter 5. An Exploration of Links between Levels of Tourism Development and Impacts on the Social Facet of Residents' Quality of Life (Elena Konovalov) -- Chapter 6. Quality of Life and Perception of the Effects of Tourism: A Contingent Approach (Nuria Porras-Bueno) -- Chapter 7. Impact of Tourism on Residents' Quality of Life: Segmentation Analysis and Marketing Implications (Celeste Eusébio) -- Chapter 8. Can Personal Values Modulate the Perception of Tourism Impacts by Local Population?: Testing for the Role of Product Identity in a Mining Tourism Destination (Andrés Artal-Tur) -- Chapter 9. Film Tourism and its Impact on Residents Quality of Life: a Multi Logit Analysis (Subhash Kizhakanveatil Bhaskaran Pillai) -- Chapter 10. Sustainable Practices in Spanish Hotels: A Response to Concerns on Quality of Life in Highly Visited Tourism Areas (Irene Gil-Saura) -- Chapter 11. The Impact of Music Festivals on Local Communities and their Quality of life: Comparation of Serbia and Hungary (Vanja Pavluković) -- Part III. Quality of Life in Tourism and its Impact on Tourists' Well-Being -- Chapter 12. Seniors: Quality of Life and Travel/Tourism (Hyelin (Lina) Kim) -- Chapter 13. The Blue Flag Label as a Tool to Improve the Quality of Life in the Sun-and-Sand Tourist Destinations (Antonio Chamorro Mera) -- Chapter 14. Impacts of Family Tourism on Families' Quality of Life - Differences According to the Family Economic Profile (Joana Lima) -- Chapter 15. A Quality-of-Life Perspective of Tourists in Traditional Wine Festivals: The Case of the Wine-Tasting Festival in Córdoba, Spain (Tomás López-Guzmán) -- Part IV. Cases Studies: From Theory to Practice on Quality of Life in Tourism -- Chapter 16. Value for Time: Slowness, a Positive way of Performing Tourism (Paola de Salvo) -- Chapter 17. Agritourism and Quality-of-Life for Farmers (Lisa Chase) -- Chapter 18. The Old Havana: Economic and Social Impact of Tourism Management on the Quality of Life of Residents (Yamilé Pérez Guilarte).
Keywords: Quality of life; Marketing; Tourism; Management; Quality of Life Research; Marketing; Tourism Management